Classification of wines according to several factors by ICP-MS multi-element analysis. (1st January 2019) - Pérez-Álvarez, E.P.; Garcia, R.; Barrulas, P.; Dias, C.; Cabrita, M.J.; Garde-Cerdán, T.
Highlights: ICP-MS could be an useful tool to classify wines according to multi-element contents. Dilution/digestion sample treatments and internal/external calibrations were assayed. The minor and trace elements did not present differences between these four methods. However, the best method was digestion with internal calibration for major elements. Sr, Ca, Mg, Mn, Ba, Ni, Cu, Cs, Pb, Zn, and Na were the wine discriminant elements. Abstract: Wines from different grape varieties, geographical zones, soil types, foliar N application, SO2 addition and oak ageing were analyzed by inductively coupled plasma mass spectrometry (ICP-MS). For this purpose, ICP-MS methodology was optimized. The elements which allowed differentiate wines from studied grape varieties were Sr, Ca, Mg and Mn. Geographical zones were classified according to Sr, Ba, Ni, and Cu. Cs and Pb were the main elements to discriminate the wines from the 3 soil types. Wines from several N foliar doses application were classified by Pb, Ni, Mn and Zn. The content of Cs, Mg, Cu and Pb in wines characterized the SO2 addition. Finally, wines storage in barrels were differentiate by Na and Cs concentration. The discriminant functions classify 100% of the wines, with the exception of grape variety (97.0%) and oak ageing (95.8%). Consequently, ICP-MS can be applied to classified wines according to viticultural and oenological factors.